Entransy in Phase-Change Systems - Gu, Junjie (SpringerBriefs in Applied Sciences and Technology, 2014)
Entransy in Phase-Change Systems summarizes recent developments in the area of entransy, especially on phase-change processes. This book covers new developments in the area including the great potential for energy saving for process industries, decreasing carbon dioxide emissions, reducing energy bills and improving overall efficiency of systems. This concise volume is an ideal book for engineers and scientists in energy-related industries.